Internal 40-gauge microneedle drainage for the management of subretinal fluid in rhegmatogenous retinal detachment surgery - Gregor S. Reiter; Jenna Krivit; Run Zhou Ye; Raymond Iezzi (International Journal of Retina and Vitreous)
Abstract Purpose To describe outcomes for internal microneedle drainage for the management of residual subretinal fluid (SRF) during pars plana vitrectomy (PPV) for rhegmatogenous retinal detachment (RRD). Methods Retrospective review of patients undergoing PPV for RRD using a 40-gauge angled and beveled microneedle (Incyto, South Korea) for the aspiration and drainage of SRF during fluid/air exchange. The microneedle is inserted through the neurosensory retina into the bleb of residual SRF, removed from the subretinal space and placed onto the retina or adjacent to the subretinal entry site. Visual acuity (VA) and safety outcomes are reported. Results Thirteen eyes from 13 patients with a median age (Q1 – Q3) of 61.12 (52.03–63.81) were included. Median visual acuity (VA) at baseline was 0.52 (0.24–0.8) logMAR (approx. 20/66) and significantly improved to 0.1 (0.02–0.26) logMAR (approx. 20/25) at the last available follow-up time point (p = 0.0167). Macula-off RRD had significantly worse VA at baseline 0.58 (0.3–1.0) logMAR (approx. 20/76) compared to macula-on RRD 0.15 (0.105–0.25) logMAR (approx. 20/28), p = 0.0196) but improved significantly to the last available follow-up (p = 0.0391), matching those with macula-on RRD. The use of microneedle drainage was safe and resulted in an attached retina in all 13 (100%) cases without adverse events. Conclusions Microneedle drainage is safe, while patient outcomes are excellent. The complete aspiration of SRF might reduce complications associated with PPV for RRD and optimize visual outcomes.